Laminatubus (Serpulidae, Annelida) from eastern Pacific hydrothermal vents and methane seeps, with description of two new species - Rouse, Greg W.; Kupriyanova, Elena K. (Zootaxa, 2021)
The bathyal serpulid Laminatubus alvini ten Hove & Zibrowius, 1986 was described from the periphery of hydrothermal vents of the Galapagos Rift and has been recorded from other vent communities of the East Pacific Rise (EPR). Here we assessed the biodiversity of serpulids collected from eastern Pacific hydrothermal vents and methane seeps using DNA sequences and morphology. Laminatubus alvini showed little genetic variation over a wide geographic range from the Alarcon Rise vents in southern Gulf of California ( 23°N), to at least a point at 38°S on the EPR. Specimens from several methane seeps off Costa Rica and the Gulf of California (Mexico) differed markedly from those of Laminatubus alvini on DNA sequence data and in having seven thoracic chaetigers and lacking Spirobranchus-type special collar chaetae, thus fitting the diagnosis of Neovermilia. However, phylogenetic analysis of molecular data showed that L. alvini and the seep specimens form a well-supported clade. Moreover, among the seep specimens there was minimally a 7% distance in mitochondrial cytochrome b sequences between a shallow-water (1000 m) seep clade restricted to Costa Rica and a deep-water clade (1800 m) from Costa Rica to Gulf of California. We describe the seep taxa here as morphologically indistinguishable L. paulbrooksi n. sp. and L. joycebrooksae n. sp.